Comparison of recovery rate in acute rinopharyngitis after antibiotic and non antibiotic treatment - Wahyudi Istiono, Beta Andewi Resti Anggraheni (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2013)
Acute rhinopharyngitis (ARI) remains become a major public health problem in the world. About 2.3 million people are diagnosed with ARI annually. In Cilacap District of Central Java, approximately 350 patients visit primary health care center due to URTI symptoms monthly. Acute rhinopharyngitis is commonly caused by viruses, therefore the use of antibiotics is not recommended. However, many evidences showed that antibiotics are prescribed to treat ARI. The aim of this study is to compare of recovery rate in acute rinopharyngitis after antibiotic and non antibiotic treatment. This was a double-blind randomized controlled trial study involving ARIs patients who visited primary health care center (Puskesmas) of Cilacap I, Cilacap District. The patients who met the inclusion and exclusion criteria were recruted and divided into two groups i.e. Treatment Group and Control Group. The Treatment Group was given symptomatic drugs and amoxicillin 500 mg three time daily for five days, while the Control Group was just given symptomatic drugs. The recovery rate of ARI patients was evaluated on the fifth day after drugs administration. One hundred and sixty six eligible ARI patients consisting 83 patients of each group were involved in this study. The results showed that the recovery rate in the Treatment Group (57 patients or 68.7%) was not significantly different with the Control Group (51 patients or 61.7%) (p = 0.417). Moreover, age, gender difference, smoking activity did not influence the recovery rate of ARI patients. However, occupation category influenced the recovery rate. In conclusion, the administration of antibiotic in ARI patients does not influence their recovery rate.Â  Â Â Key words : acute rinopharyngitis Â - management â symptomatic drugs - antibiotic - recovery rate